Benign Neglect or Malign Select?: Entry Cost to GATS/WTO - KeukJe Sung (East Asian Economic Review (EAER), 2018)
WTO was established in 1995 and as many as 36 new members joined WTO until December 2017. Thus it would be interesting to see if new members have committed higher or lower levels of market opening compared to the original members. In this regard, a sophisticated scoring scheme is needed to quantify market opening commitments. After proper econometric model is established for the original members, same model can be applied to the new members for comparison. It was found that new members committed a much higher level of commitment than the original members. In addition, it was also found that transition economies committed higher levels than the non-transition economies. More interesting finding is that among the new members, the larger the economies or the larger the trading volume are, the closer was the level of commitment to the predicted level. Then the question is whether this difference was due to benign neglect by the new members or due to malign select by the original members.
Keywords: F13; F14; L80; 330; GATS; WTO; Entry Cost; Specific Commitments; Newly Acceding Members